If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7c + -7b = x Reorder the terms: -7b + 7c = x Solving -7b + 7c = x Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-7c' to each side of the equation. -7b + 7c + -7c = -7c + x Combine like terms: 7c + -7c = 0 -7b + 0 = -7c + x -7b = -7c + x Divide each side by '-7'. b = c + -0.1428571429x Simplifying b = c + -0.1428571429x
| 3(x+7)-4(x+3)=10 | | 12+50=949.88 | | 6y+(-4)= | | -2x=5x-9x+16-10 | | 7=.75*20+4 | | -3/4*8 | | 3+66x=33x+22 | | -x/4=-22 | | 4(7x+1)=312 | | .6h=1.8 | | 2(3y-6)= | | 8x+3y=101 | | -4(8+5x)=-32 | | 14=4a+2 | | 5x+11=7-2x | | -94=-2(5m+7) | | -2(7x-5)+3=-14x+13 | | p/7=6.8.k/4=2 | | 3x+11=12+8x | | 193=-x+96 | | -9x-13=50 | | 60x-3x^/3x | | 7(2x+2)=-84 | | 6x-8=6(x-5) | | 23=8*1+y | | 6460-h=4181 | | 1/4=b=3.4 | | 4.6d=26.68 | | 16x-6x=56 | | 10x+7=3x+15 | | 2/3(6x-12)=-16 | | 2/3(6x-12)=- |